A Model for Xml-based Electronic Health Record System - N., Gayathri; A. , Priya; S. , Sridhar; G. , Charlyn Pushpa Latha (International Journal of Psychosocial Rehabilitation, 2020)
Cloud-based electronic health record (EHR) frameworks change medicinal reports to be exchanged between medical institutions; this can be relied upon to add to improvements in various therapeutic administrations; this can be expected to contribute enhancements in numerous medical services in the future. However, because the system design becomes more difficult, cloud-based EHR systems might introduce further security threats in comparison to existing singular systems. Thus, patients privacy in any healthcare system that’s supported the quality of every patient within the health record system. So as to shield the privacy of patients, several approaches are planned to produce access management to patient documents once providing health services. However, most current systems don’t support fine-grained access management or take into consideration further security factors like coding and digital signatures. In this paper, we’ve a bent to propose a cloud-based EHR model that performs attribute-based access management exploitation of extensible access management language. Our EHR exhibit on security performs fractional mystery composing and uses electronic marks once a patient record is circulated to a report requester. We have a tendency to use XML coding and XML digital signature technology. Our planned model works expeditiously and solely provides the mandatory data to requesters, who are for more efficiency and increased patient safety.